ANALISA KESESUAIAN MASUKAN HEAT INPUT PADA PENGELASAN GTAW UNTUK MATERIAL SOLID INCONEL UNS N06625 - Hilmy, Zakwan; Susilo, Trisno; Tyas Adi, Fajar; Milang Aran, Mikhael (JURNAL JALASENA, 2024)
Currently metal joining (welding) is widely needed in the world of fabrication, mining and shipping construction. Good welding has a guiding procedure in the form of WPS. WPS has several parameters that determine heat input. This research was conducted to determine the compatibility between the parameters in the procedures used and the actual parameters used in the field. The research was carried out on 3 samples that had the same dimensions, namely a diameter of 4" with a thickness of 6.02 mm. The three samples were welded by three different welders with the same qualifications. The research results found that the actual parameters used were not too far from those stated in the WPS. The welds are then checked visually and then continued with the NDT process in the form of RT & PMI. This is done to determine the condition of the inside of the weld and its chemical composition after the welding process